Finding Meaning in Motherhood and Examining the Sense of Self through the Lived Experiences of First-Time Mothers - Absara, Ailyn Sabdilon (Animo Repository, 2023)
Becoming a mother signifies an important transition for a woman. This study followed 30 first-time mothers through their third trimester of pregnancy and the first two months into the transition to motherhood and explored their lived experiences. The chief concern of the study is to explore how this transition experience impacts the woman's sense of self and how these experiences enable the realization of the meaning of motherhood. An interpretative phenomenological analysis is used in the study. In the last trimester, lived experiences described four organizing themes: confirmation of the pregnancy, vulnerability, expectations and practices in pregnancy and childbirth, and lastly, ideals of motherhood. Two months post-partum, the lived experiences also described four organizing themes: realization of the new motherhood identity, vulnerability, expectations,and lastly, the world revolving around the baby. As for the woman's sense of self in first- time motherhood, a personal and a relational self emerged. Realizations attributed to own characteristics discovered are described in the personal self, whereas realizations attributed to interpersonal characteristics are described in the latter. Lastly, the meaning of motherhood was described in three organizing themes: experiences in transition, transformations, and training. Integration of results and their implications are discussed.